Simultaneous regulation of cations and anions in an electrolyte for high-capacity, high-stability aqueous zinc–vanadium batteries - Wang, Ziqing; Zhou, Miao; Qin, Liping; Chen, Minghui; Chen, Zixian; Guo, Shan; Wang, Liangbing; Fang, Guozhao; Liang, Shuquan (eScience (Beijing), 2022)
Safe, inexpensive aqueous zinc-ion batteries (AZIBs) are regarded as promising energy storage devices. However, they still face issues, including dissolution and collapse of the cathode as well as H2 evolution and the growth of Zn dendrites on the Zn anode. Herein, we simultaneously regulate the cations and anions in the electrolyte for high-capacity, high-stability aqueous zinc–vanadium (Zn–V) batteries based on a bimetallic cation-doped Na0.33K0.1V2O5⋅nH2O cathode. We demonstrate that Na+ ​cations suppress cathode dissolution and restrain Zn dendrite growth on the anode via an electrostatic shield effect. We also illustrate that ClO4− anions participate in energy storage at the cathode and are reduced to Cl−, generating a protective layer on the Zn anode surface and providing a stable interface to decrease Zn dendrites and H2 evolution during long-term cycling. When Na+ and ClO4− are introduced into an aqueous ZnSO4 electrolyte, a Zn/Zn symmetric cell shows durable and reversible Zn stripping/plating for 1500 ​h at a current density of 1 ​mA ​cm−2 and with an area capacity of 1 mAh cm−2. Zn/Na0.33K0.1V2O5⋅nH2O full batteries exhibit a high capacity of 600 mAh g−1 at 0.1 ​A ​g−1 and long-term cycling performance for 5000 cycles, with a capacity of 200 mAh g−1 at 20 ​A ​g−1. [Display omitted] •Simultaneously regulating the cation and anion in the electrolyte toward high-performance aqueous zinc-vanadium batteries.•Cation Na+ suppresses the dissolution of the cathode and restrains the Zn dendrite on the anode.•Anion ClO4− participates in the energy storage at the cathode and is reduced to Cl− forming a protective layer on the anode.